Qur'anic Concept in Managing the Relation of Human and Nature to Avoid the Nature Damage - Andini, Riddo; Rahmat, Rahmat; Affan, Fikri Muhammad; Uldiman, Uldiman (Khalaqa: Journal of Education and Learning, 2023)
This paper intends to reveal the ideas and concepts contained in the Qur'an related to environmental issues. Where the Qur'an provides a new solution or alternative related to this environmental issue whose purpose is to educate people so that they treat nature wisely. The Qur'an sees the need for a preventive effort to overcome environmental problems by increasing harmonization between humans and nature. The results of this study refute the opinion of Immanuel Kant (practical philosophy, 1999) who asserts that only humans are rational beings, so it is permissible to use other non-rational beings to achieve human life goals. Since beings other than humans and all other natural entities lack reason, they have no right to be treated morally towards them. At the same time supporting the opinion of Seyyed Hossein Nasr (1996), who stated that the current environmental crisis is not a religion's fault, but a human error that has abandoned spiritual traditions. The method used in this study is the maudū'i (thematic) interpretation method formulated by Rasywānī, using an integrative-interconnective approach in an effort to understand the complex phenomena of life faced and lived by humans.